3(2z)=-3

Simple and best practice solution for 3(2z)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2z)=-3 equation:


Simplifying
3(2z) = -3

Remove parenthesis around (2z)
3 * 2z = -3

Multiply 3 * 2
6z = -3

Solving
6z = -3

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Divide each side by '6'.
z = -0.5

Simplifying
z = -0.5

See similar equations:

| -690=10(-7x+22) | | 5x-9x+3=17 | | 8x-4(-3+2)=-12 | | 2m+6n-9(5m-4n)= | | (2x-8)(2x-8)=44 | | 12x+15y=90 | | 100-66=31y-35y | | 10=-x+2y | | 2x-18=9x+6 | | 7.57x+22.71=45.42 | | 5+3t-3=8t+14-3t | | (X+14)=(x-20) | | 25=2(x+3) | | 2x+2(x-28)=-104 | | 2x-1-x=9x-3 | | -18+10=-17s | | (x+4)(x-4)=4 | | 5+y=0.0024x | | 3x+2(x-28)=-104 | | y=3x^2-6x+200 | | 2x-8(2x-8)=44 | | 25u+75=23u+92 | | (X+10)=(x-11) | | -7-0.83x=18 | | 4x+b=ax+9 | | (X-11)=(2x-42) | | 16x=180+12y | | .8v+3.2=2.4-v | | (X+10)=(2x-42) | | 2x+5-x=3(2-x)+7 | | 9x-55=110-2x | | -(1+6m)-8=-7(m+1) |

Equations solver categories